Pengaruh Penggunaan Platform Microsoft Teams Terhadap Hasil Belajar Siswa Di SMK Negeri 1 Karawang - Sri Rahayu; Mohammad Afnan; Budi Kudwadi (Universitas Pendidikan Indonesia, 2021)
Direct face-to-face instruction isn't permitted amid the Covid-19 widespread, so these exercises are exchanged online. Microsoft Teams may be a advanced stage that can encourage online bunch assembly exercises. The utilize of these applications is applied to learning exercises for street and bridge development subjects within the trust of progressing understudy learning results. The reason of this think about is to discover out:Overview of the utilize of Microsoft Groups application at SMK Negeri 1 Karawang,Overview of understudy learning results in street and bridge construction subjects, Impact of utilizing Microsoft Groups application on learning results understudies within the subject of street and bridge development at SMK Negeri 1 Karawang. The investigate strategy this time is to apply quantitative investigate utilizing correlational investigation methods. The information collection strategy for utilizing the Microsoft Groups application (variable X) employments a survey, whereas information on understudy learning victory (variable Y) employments documentation of understudy scores within the Street and Bridge Development subject. The results of this study this consider appear that (1) The common depiction of the utilize of the Microsoft Groups application is categorized as direct with a rate of 40% (2) Understudy learning results in Street and Bridge Development subjects at SMK Negeri 1 Karawang appear a good category, (3) There's an impact the utilize of the Microsoft Groups application on understudy learning results outcomes significantly with regression equation Y = 24.660 + 0.517X, andthe contribution of the X variable to the Y variable is 26.3%.